2011
DOI: 10.1016/j.ajpath.2010.11.066
|View full text |Cite
|
Sign up to set email alerts
|

Nodal Signals through Activin Receptor-Like Kinase 7 to Inhibit Trophoblast Migration and Invasion

Abstract: Trophoblast cell invasion into the uterus is an essential process for successful pregnancy, and shallow invasion of trophoblasts into the maternal decidua is linked to preeclampsia. We have reported that Nodal, a member of the transforming growth factor-␤ superfamily, acts through activin receptor-like kinase 7 (ALK7) to inhibit trophoblast proliferation and to induce apoptosis. In this study, we examined the spatial and temporal expression patterns of Nodal and ALK7 in human placenta from normal and preeclamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(108 citation statements)
references
References 43 publications
7
101
0
Order By: Relevance
“…For example, it has been shown that Nodal upregulation induces apoptosis and inhibits proliferation of a trophoblast cell line (HTR8/SVNeo) leading to reduced invasion (Munir et al, 2004). More importantly, Nodal has also been found to be increased in placentas from pre-eclamptic patients (Nadeem et al, 2011). In this study we furthermore observed that reduced Nodal activity in the maternal decidua induced Activin-A transcription leading to increased levels of Activin-A excretion.…”
Section: Discussionsupporting
confidence: 62%
“…For example, it has been shown that Nodal upregulation induces apoptosis and inhibits proliferation of a trophoblast cell line (HTR8/SVNeo) leading to reduced invasion (Munir et al, 2004). More importantly, Nodal has also been found to be increased in placentas from pre-eclamptic patients (Nadeem et al, 2011). In this study we furthermore observed that reduced Nodal activity in the maternal decidua induced Activin-A transcription leading to increased levels of Activin-A excretion.…”
Section: Discussionsupporting
confidence: 62%
“…Therefore, hESC-derived trophoblasts are capable of forming iCTBs or STBs when exposed to relevant extracellular cues, similar to human placental trophoblasts. Other functional properties of first and third trimester trophoblasts and mouse trophoblasts have been reported, such as their differential response to nodal and activin treatment (58,(73)(74)(75)(76). These should also be tested in hESC-derived trophoblasts, although these studies are beyond the scope of this work.…”
Section: Discussionmentioning
confidence: 99%
“…It is known, for example, that Nodal signalling can maintain pluripotency and prevent differentiation to neuroectoderm in human embryonic stem cells (hESC) and mouse epiblastderived stems cells (mEpiSC) [32] while it is necessary for endoderm differentiation in pluripotent cells and the mouse gastrula embryo [3,33]. Similarly, Nodal can inhibit cell migration, invasion and proliferation in human trophoblasts [34,35] while it promotes the opposite in human glioma and breast cancer cells [36,37]. Such divergent mechanisms create the necessity of developing a conceptual framework to help recognize L-R patterns and assess the phenomenon in a meaningful manner.…”
Section: Context-dependency Of Nodal Functions In Nervous System Asymmentioning
confidence: 99%